Inventing the Cloud Century : How Cloudiness Keeps Changing Our Life, Economy and Technology /: How Cloudiness Keeps Changing Our Life, Economy and Technology. ([2018]) - Oppitz, Marcus; Tomsu, Peter
No abstract available